A randomised controlled double‐blind clinical trial of 17‐hydroxyprogesterone caproate for the prevention of preterm birth in twin gestation (PROGESTWIN): evidence for reduced neonatal morbidity. (27th August 2014) - Awwad, J; Usta, IM; Ghazeeri, G; Yacoub, N; Succar, J; Hayek, S; Saasouh, W; Nassar, AH
<x xml:space="preserve">Abstract</x> Objective To determine whether 17 alpha‐hydroxyprogesterone caproate (17OHPC) prolongs gestation beyond 37 weeks of gestation (primary outcome) and reduces neonatal morbidity (secondary outcome) in twin pregnancy. Design Randomised controlled double‐blind clinical trial. Setting Tertiary‐care university medical centre. Population Unselected women with twin pregnancies. Methods Participants received weekly injections of 250 mg 17OHPC (n = 194) or placebo (n = 94), from 16–20 to 36 weeks of gestation. Randomisation was performed using the permuted‐block randomisation method. Data were analysed on an intention‐to‐treat basis. Main outcome measure Preterm birth (PTB) rate before 37 weeks of gestation. Results There were no significant differences in the average gestational age at delivery, or in the rates of PTB before 37, 32, and 28 weeks of gestation, between the two groups. The proportion of very‐low‐birthweight neonates (<1500 g) was significantly lower in the 17OHPC group (7.6%) compared with placebo (14.3%) (relative risk, RR 0.5; 95% confidence interval, 95% CI 0.3–0.9; P = 0.01). Progestogen‐treated neonates had a significantly lower composite neonatal morbidity (19.1%) compared with placebo (30.9%) (odds ratio, OR 0.53; 95% CI 0.31–0.90; P = 0.02), with significantly lower odds for respiratory distress syndrome (14.4 versus 23.4%; OR 0.55; 95% CI 0.31–0.98; P = 0.04), retinopathy of prematurity (1.1 versus 4.6%; OR 0.21; 95% CI 0.05–0.96; P = 0.04), and culture‐confirmed sepsis (3.4 versus 12.8%; OR 0.24; 95% CI 0.10–0.57; P = 0.00). Conclusions Intramuscular 17OHPC therapy did not reduce PTB before 37 weeks of gestation in unselected twin pregnancies. Nonetheless, 17OHPC significantly reduced neonatal morbidity parameters and increased birthweight.